Die Kämpfer unter der weissen Fahne : (Bertha von Suttner und die slowakischen Tolstoisten in Oberungarn) - Mária Bátorová (Opera slavica)
The article describes the literary and public struggle of Bertha von Suttner for peace and the impact of her activity on the Slovak Tolstoists. The relation of Bertha von Suttner to L. N. Tolstoi and to the Slovak Tolstoists are also discussed.